Black carbon emissions from flaring in Russia in the period 2012–2017. (1st June 2021) - Böttcher, Kristin; Paunu, Ville-Veikko; Kupiainen, Kaarle; Zhizhin, Mikhail; Matveev, Alexey; Savolahti, Mikko; Klimont, Zbigniew; Väätäinen, Sampsa; Lamberg, Heikki; Karvosenoja, Niko
Abstract: Gas flaring in the oil and gas industry has been identified as an important source of anthropogenic black carbon (BC) affecting the climate, particularly in the Arctic. Our study provides spatially-explicit estimates of BC emissions from flaring in Russia utilising state-of-the-art methodology for determining the emission factors. We utilised satellite time series of the flared gas volume from Visible Infrared Imaging Radiometer Suite (VIIRS) for the period 2012 to 2017, supplemented with information on the gas and oil field type. BC emissions at flaring locations were calculated based on field type-specific emission factors, taking into account different gas compositions in each field type. We estimate that the average annual BC emissions from flaring in Russia were 68.3 Gg/year, with the largest proportion stemming from oil fields (82%). We observed a decrease in the yearly emissions during the period 2012 to 2017 with regional differences in the trend. Our results highlight the importance of detailed information on gas composition and the stage of oil and gas separation of the flared gas to reduce uncertainties in the BC emission estimates. Graphical abstract: Image 1 Highlights: New estimate for black carbon emissions from flaring in Russia. Enhanced temporal profiles of flared gas volume from VIIRS. Oil and gas field-type specific emission factors developed. Average BC emissions from 2012 to 2017 are estimated at 68.3 Gg/year.